The Effect of Meaning of Work and Psychological Empowerment on Affective Commitment with Work Engagement as an Intervening Variable - Diniyati, Lia; Sudarma, Ketut (Universitas Negeri Semarang, 2018)
This study aimed to determined the effect of meaning of work (X1) and psychological empowerment (X2) on affective commitment (Y2) with work engagement (Y1) as an mediating variable of Kesambi Hijau Hotel employees Semarang. This research is quantitative research. The population in this research is 49 employees. Sampling in this research using saturated sampling system, obtained sample size that must be used is 49 employees. Analytical methods used are instrument test (validity and reliability), classical asumption test, multiple linear regression test, and path analysis test with SPSS version 21. Data collection method using interview, qustionnaire, and library study. The results showed that all of hypothesis could be accepted. The results of this study demonstrated that meaning of work and psychological empowerment had a significant positive effect on affective commitment. Meanwhile, work engagement could be a mediating variable in the relationship between work engagement and psychological empowerment on affective commitment. Suggestion from this research that the organization should motivate employees to have spirit to achieve the goals and ilvolve employees in decision making so employees eill feel bound so that employees affective commitment will also increase.